2021
DOI: 10.1007/s00436-021-07266-w
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation and in vivo efficacy of nitroimidazole-sulfanyl ethyl derivatives against Leishmania (V.) braziliensis and Leishmania (L.) mexicana

Abstract: The aim of this study was to synthesize several small molecules of the type 5-nitroimidazole-sulfanyl and evaluate biological properties against the main Leishmania species that cause cutaneous leishmaniasis in Venezuela. Final compounds 4-7 were generated through simple nucleophilic substitution of 1-(2-chloroethyl)-2-methyl-5-nitroimidazole 3 with 2-mercaptoethanol, 1-methyl-2-mercaptoethanol, and 2-thyolacetic acid derivative. Compound 8 was synthesized via a coupling reaction between 7 and (S)-Methyl 2-ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…As a result, an in vivo evaluation was conducted using mouse models of cutaneous leishmaniasis (CL). This evaluation showed that both compounds reduced 96% of the lesions and cured 63% of the mice [32]. Recent studies have been directed toward quinoline and metronidazole hybrids as a potential solution for VL.…”
Section: Metronidazole Derivativesmentioning
confidence: 93%
See 3 more Smart Citations
“…As a result, an in vivo evaluation was conducted using mouse models of cutaneous leishmaniasis (CL). This evaluation showed that both compounds reduced 96% of the lesions and cured 63% of the mice [32]. Recent studies have been directed toward quinoline and metronidazole hybrids as a potential solution for VL.…”
Section: Metronidazole Derivativesmentioning
confidence: 93%
“…As a result, an in vivo evaluation was conducted using mouse models of cutaneous leishmaniasis (CL). This evaluation showed that both compounds reduced 96% of the lesions and cured 63% of the mice [32]. Subsequently, they found that compounds 55c, 60, 61, and 62 reduced the growth of promastigotes of L. mexicana and L. braziliensis, and they measured the mean inhibitory concentrations (IC 50 ) against intracellular amastigotes of both species (Table 8).…”
Section: Metronidazole Derivativesmentioning
confidence: 97%
See 2 more Smart Citations